PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE CONCEPT SENTENCE BERBANTUAN MEDIA POP-UP BOOK TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI PESERTA DIDIK DI SEKOLAH DASAR - Feby Inggriyani; Dindin MZM; Ananda Nur Azizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by the problems determined in class IV at SDN 017 Sekejati Bandung City, namely the low skills of students in writing narrative essays. The type of research is a quantitative approach with a type of pseudo-experimental research or quasi experiment with a nonequivalent control group design. The research population used all fourth grade students of SDN 017 Sekejati, and the samples were class IVA as the experimental class and class IVB as the control class. The instrument used is in the form of test data on students' narrative essay writing skills. The results showed that the effect size test value of the post-test data was 0.6 with a large category. Thus, it is concluded that there is a great influence of the Concept Sentence type cooperative learning model assisted by Pop-Up Book media on students' narrative essay writing skills in elementary schools. Keywords: concept sentence cooperative learning model, narrative writing skills, pop-up book